The expression of Ki-67 and clinicohistopathological characteristics of breast cancer in Southern Sumatra, Indonesia - Harist, Muhammad; Wresnindyatsih; Fertilita, Soilia; Prasetyo, Nauval Togi; Abdurrachman, Muhammad Rafi (Faculty of Medicine, Universitas Islam Indonesia, 2024)
Background: Breast cancer is the most frequently diagnosed cancer in the world, approximately 2.3 million new cases (11.7% of all cancer cases) per year in 2020. The Ki-67 expression is clinically used to classify molecular subtypes of breast cancer into luminal A and luminal B groups.Objectives: This study aimed to investigate relationships between clinicohistopathological characteristics (ages, histopathological types, histopathological grades, molecular subtypes) of breast carcinoma patients and the Ki-67 proliferation index at dr. Moh. Hoesin General Hospital (RSMH) Palembang in 2019–2021.Method: This study applied an observational analytic study with a cross-sectional approach. 521 samples were included in this study based on inclusion and exclusion criteria. The samples in this study included invasive breast carcinoma patients who underwent histopathological examination and immunohistochemistry (IHC), recorded in the medical records at RSMH Palembang for 2019–2021 period. Then a statistical analysis was performed by using the chi-square test, which was analysed in the SPSS application.Results: The correlation between Ki-67 proliferation index and histopathological grades was statistically significant (p=0.018). The Ki-67 proliferation index was also statistically significantly associated with the molecular subtypes (p=0.000). Neither age (p=0.315) nor histopathological types (p=0.417) were significantly associated with the Ki-67 proliferation index.Conclusion: The Ki-67 expression was significantly associated with histopathological value and molecular subtype in breast carcinoma patients at RSMH Palembang in 2019–2021. The Ki-67 expression was not associated with the clinic-histopathological characteristics of ages and histopathological types.